2016
DOI: 10.1037/xhp0000254
|View full text |Cite
|
Sign up to set email alerts
|

Conjoint influence of mind-wandering and sleepiness on task performance.

Abstract: Recent research suggests that sleepiness and mind-wandering-the experience of thoughts that are both stimulus-independent and task-unrelated-frequently co-occur and are both associated with poorer cognitive functioning. Whether these two phenomena have distinguishable effects on task performance remains unknown, however. To investigate this question, we employed the online experience sampling of mind-wandering episodes and subjective sleepiness during a laboratory task (the Sustained Attention to Response Task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
41
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 107 publications
(180 reference statements)
15
41
5
Order By: Relevance
“…In other situations, however, mind wandering and mind blanking can be differentiated by arousal levels such that mind blanking is still associated with lowered arousal, but mind wandering is associated with heightened arousal. This finding is similar to recent research by Stawarczyk and D'Argembeau (2016), who found that mind blanking was associated with higher levels of drowsiness than was mind wandering, suggesting that mind blanking and mind wandering are distinguishable. Thus, in many attention-demanding situations, mind wandering and mind blanking are likely similar.…”
Section: Discussionsupporting
confidence: 91%
“…In other situations, however, mind wandering and mind blanking can be differentiated by arousal levels such that mind blanking is still associated with lowered arousal, but mind wandering is associated with heightened arousal. This finding is similar to recent research by Stawarczyk and D'Argembeau (2016), who found that mind blanking was associated with higher levels of drowsiness than was mind wandering, suggesting that mind blanking and mind wandering are distinguishable. Thus, in many attention-demanding situations, mind wandering and mind blanking are likely similar.…”
Section: Discussionsupporting
confidence: 91%
“…We also obtained subjective reports of arousal after each baseline period using the same arousal scale as in Åkerstedt and Gillberg (1990) and Stawarczyk and D'Argembeau (2016).…”
Section: Locus Coeruleus and Fluid Intelligence 58mentioning
confidence: 99%
“…One possible explanation for these findings could be that less self-relevant stimuli induce mind-wandering. Mind-wandering is defined as the occurrence of self-generated thoughts that are both unrelated to the current task and decoupled from immediate sensory perceptions [ 20 , 21 ]. It is known that mind-wandering caught by a probe distracts attention to stimuli in an ongoing task, which was associated with longer reaction times [ 20 ].…”
Section: Discussionmentioning
confidence: 99%